Role of hydrocortisone and pheniramine as prophylaxis against adverse drug reaction to snake antivenom - Yaqoob, Arjimand; Mufti, Showkat A.; Ashraf, Sharika (International Journal of Advances in Medicine, 2021)
Background: Antivenom remains the primary treatment for any patient with serious snake envenomation and in most patients should be used whenever indicated. Reactions to most antivenom preparations are common. Evidence does not support routine pre-treatment with either antihistamines or corticosteroids. Methods: This hospital based retrospective and prospective comparative study was conducted at Sher-i-Kashmir Institute of Medical Sciences, Srinagar. In our study 108 patients were studied. Patients in group A received premedication with injection hydrocortisone 100 mg and injection pheniramine 25 mg intravenous (IV) stat before anti-snake venom (ASV). Patients in group B did not receive any premedication. Adverse reactions to ASV was compared in two groups. Results: Out of 108 patients, 105 (97.22%) required ASV. Fifty nine were retrospective cases (group A) who had received premedication with hydrocortisone and pheniramine. Forty six patients were studied prospectively, who received ASV (group B) with no premedication. In group A, no patient developed adverse reaction to ASV. 3 patients (6.52%) in group B developed adverse reaction to ASV. Conclusions: Premedication with hydrocortisone and pheniramine do not prevent adverse reactions to ASV significantly. Adverse reactions to ASV were low in our study to comment fully on role of premedication to prevent these reactions.